Validating Regulatory Sensory Processing Disorders Using the Sensory Profile and Child Behavior Checklist (CBCL 1 –5) - Pérez-Robles, R (2014)
The objective was to validate Regulatory Sensory Processing Disorders’ criteria (DC:0-3R, 2005) using empirical data on the presence and severity of sensory modulation deficits and specific psychiatric symptoms in clinical samples. Sixty toddlers who attended a child mental health unit were diagnosed by a clinical team. The following two groups were created: toddlers with RSPD(N = 14) and those with ‘‘other diagnoses in Axis I/II of the DC:0-3R00(OD3R) (N = 46). Independently of the clinical process, parents completed the Infant Toddler Sensory Profile (as a checklist for sensory symptoms) and the Achenbach Behavior Checklist for ages 1/2–5 (CBCL 1/2–5). The scores from the two groups were compared. The results showed the following for the RSPD group: a higher number of affected sensory areas and patterns than in the OD3R group; a higher percentage of sensory deficits in specific sensory categories; and a higher severity of behavioral symptoms such as withdrawal, inattention, other externalizing problems and pervasive developmental problems in CBCL 1/2–5. The results confirmed our hypotheses by indicating a higher severity of sensory symptoms and identifying specific behavioral problems in children with RSPD. The results revealed convergent validity between the instruments and the diagnostic criteria for RSPD and supported the validity of RSPD as a unique diagnosis. The findings also suggested the importance of identifying sensory modulation deficits in order to develop an early intervention to enhance the sensory capacities of children who do not fully satisfy the criteria for some DSM-IV-TR disorders.